Edukasi Pencegahan Penyakit Demam Berdarah Dengue (DBD) melalui Kelompok “Sobat Lawan Jentik” di SMP Negeri 7 Tasikmalaya - Setiyono, Andik; Maulidi Tanjung, Muhamad Fajar (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Dengue hemorrhagic fever (DHF) continues to be a significant public health concern worldwide, including in Indonesia. The highest incidence of fatal cases due to dengue fever is observed among school-aged children. Consequently, the eradication of mosquito nests (PSN) is imperative to prevent dengue fever. The efficacy of the prevention program is attributable to its success in empowering the community, including educational institutions, through the establishment of jumantik cadres. The objective of this initiative is to enhance the knowledge and attitudes of jumantik cadres, specifically the "Sobat Lawan Jentik" group, in the prevention of DHF disease through mosquito nest eradication (PSN). The method employed entails the delivery of health education pertaining to dengue disease, with a particular emphasis on its prevention, and the implementation of the mosquito nest eradication program (PSN). The evaluation strategy encompassed a pre-test and post-test phase, complemented by a response questionnaire that addressed the activities undertaken. The results of this activity have succeeded in significantly increasing the knowledge of participants (p value = 0.001). This activity has been demonstrated to have a substantial impact on the attitude value of participants (p=0.001). This activity has been shown to positively influence participants' knowledge and attitudes. According to the findings of the questionnaire, the majority of the participants regarded this activity as highly beneficial.